Early experience of heart-lung transplantation. Issue 9 (September 1989) - Smyth, R L; Higenbottam, T W; Scott, J P; McGoldrick, J P; Whitehead, B; Helms, P; de Leval, M; Wallwork, J
Abstract : We report our experience of heart-lung transplantation for the treatment of children with terminal respiratory disease. Between May 1987 and October 1988 we performed heart-lung transplantation in five children under the age of 16 (age range 11-15). All the patients were severely disabled by dyspnoea and hypoxia. Two had primary pulmonary hypertension, two cystic fibrosis, and one had Eisenmenger's syndrome. All five children are alive and well five to 17 months after operation and have returned to activities normal for their age. Three of the five patients had episodes of infection after operation. These were staphylococcal pneumonia, herpes simplex pneumonitis and, in one of the patients with cystic fibrosis, persistent purulent sputum. The mean number of episodes of rejection per child was 2.7 per half year. Heart-lung transplantation is a practical treatment for children in these disease groups with terminal respiratory failure.